2017
DOI: 10.1097/jtn.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Certification Matters

Abstract: As professionals, we have many opportunities to prove our expertise in our field. Professional Certification is one of those opportunities. Certified nurses have reported feeling more empowered, with better collaborative relationships, as well as believing that they provide better care. Nurses also have perceived intrinsic value to obtaining certification in a specialty practice area. The certification process attempts to demonstrate that the nurse has exceeded the minimal standards and exhibits a high level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Intrinsic values relate to certification refer to personal accomplishments that are related to empowerment, improved work effectiveness, commitment to the nursing profession, and higher levels of clinical competence. [10][11][12] Extrinsic values relate to certification refer to employer and community recognition resulting in more collaboration and recognition by others. [9][10][11] Studies have demonstrated the perceived value of certification among several nursing specialties 9,[13][14][15] ; however, no studies have evaluated the perceived value of certification among SCRNs or CNRNs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic values relate to certification refer to personal accomplishments that are related to empowerment, improved work effectiveness, commitment to the nursing profession, and higher levels of clinical competence. [10][11][12] Extrinsic values relate to certification refer to employer and community recognition resulting in more collaboration and recognition by others. [9][10][11] Studies have demonstrated the perceived value of certification among several nursing specialties 9,[13][14][15] ; however, no studies have evaluated the perceived value of certification among SCRNs or CNRNs.…”
mentioning
confidence: 99%
“…[10][11][12] Extrinsic values relate to certification refer to employer and community recognition resulting in more collaboration and recognition by others. [9][10][11] Studies have demonstrated the perceived value of certification among several nursing specialties 9,[13][14][15] ; however, no studies have evaluated the perceived value of certification among SCRNs or CNRNs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through this certification, the profession validates a higher level of clinical knowledge beyond the nursing licensure. As a Magnet hospital, and as supported in the literature, professional certification should be a significant contributor in advancement 12 …”
Section: Cap Redesignmentioning
confidence: 99%
“…As a Magnet hospital, and as supported in the literature, professional certification should be a significant contributor in advancement. 12 The literature review highlighted the importance of career advancement within CAPs. 4 An aim of the redesign was to create a means for nurses to increase collaboration throughout the institution and tailor their advancement to specific areas of interest.…”
Section: Cap Redesignmentioning
confidence: 99%